Plakat "Nein - zur kapitalistischen Ausbeutung!" - Efimov, B.
politischer Rahmen;politisches Leben (allgemein);politische Ideologie;Kapitalismus politischer Rahmen;politisches Leben (allgemein);politische Ideologie;Sozialismus